Design and Research on the Mechanical Structure of a Heavy-Duty Hexapod Robot with Bouncing Characteristics - Zhang, Zeyu; Wang, Jiaju; Wang, Shiyun (International Journal of Mechanical and Electrical Engineering, 2024)
Based on the lunar exploration project, a mechanical structure design scheme for a heavy-duty hexapod robot movement system with bounce characteristics was proposed. The materials used were determined by the robot's working environment and performance standards. The mechanical structure of a jumping heavy-duty hexapod robot was designed using SolidWorks 3D modeling software. Based on the analysis of the working modes of the root joint, hip joint, knee joint, and jumping energy storage mechanism, the main components of each joint and jumping energy storage mechanism were designed, and a single leg mechanism was obtained. Based on the special soil structure on the lunar surface, the foot end buffer mechanism was designed, and finite element stress analysis was conducted on the key components of the robot model, proving the rationality of the mechanical structure of a heavy-duty hexapod robot with bounce characteristics.